Dietary effect of different drying methods and graded inclusion levels of ginger (zingiber officinale) on the perfonnance and gut morphology of broilers (2016)
The experimental design was a 3 by 3 factorial arrangement in a completely randomized design. Three hundred broilers were used for the experiment; they were randomly allotted to the ten dietary treatments with 5 replicates per treatment and 6 birds per replicate. The birds were weighed weekly to determine their weight gain, body weight and feed conversion ratio. Thirty finisher birds were sacrificed and the ileum and duodenum removed for gut histo-morphometry. Results showed that drying methods influenced performance. This was observed for the average body weight gained per bird per day while the effect of the inclusion level was observed on the feed conversion ratio. Factor interaction was observed for weight gained/bird per day and feed conversion ratio. However, only numerical differences were observed for average final body weight/bird and average feed intake /bird/day. Duodenal and ilea, villous height showed significant effect (P<0.05) of drying method, inclusion levels and treatment interaction with the control having the highest mean values. It can be concluded that supplementing broiler feed with air-dried ginger at 1.5% inclusion level can be effective as it led to an increase in the final body weight, average body weight gained per day per bird and average feed intake. No effect of drying methods and inclusion levels were observed for the histo-morphometry.